Beyond Wage as a Major Determinant of Occupational Choice in the Entertainment and Sports Industry - Junior, F.S. (University of Ghana, 2013)
Wages and earnings have been a constant source of interest to labour economists. This study investigates the influence of non-pecuniary factors like personality traits, prestige, education, parents among others on occupational choice using primary data collected from a survey of 150 purposive sampled professionals in the entertainment and sports industry in Ghana. A multinomial logit (MNL) analysis was conducted to examine the significance and marginal effects of these non-pecuniary variables on the individual’s choice of occupation. The data provide extensive information on the socioeconomic characteristics of the individuals as well as the empirical results from the MNL analysis. The results from the estimation using a multinomial logit model was linked with some literature and also checked against apriori assumptions. Generally, the findings indicate that education and training, and geographical context had higher marginal influence on the choice of both football and acting career in relation to the base (music) than other factors in the model. Some of the variables conformed to apriori expectation, albeit insignificant.
Thesis (MPHIL)-University of Ghana, 2013